2015
DOI: 10.1039/c4nr06824f
|View full text |Cite
|
Sign up to set email alerts
|

Direct patterning of nanoparticles and biomolecules by liquid nanodispensing

Abstract: We report on the localized deposition of nanoparticles and proteins, nano-objects commonly used in many nanodevices, by the liquid nanodispensing (NADIS) technique which consists in depositing droplets of a solution through a nanochannel drilled at the apex of an AFM tip. We demonstrate that the size of spots can be adjusted from microns down to sub-50 nm by tuning the channel diameter, independently of the chemical nature of the solute. In the case of nanoparticles, we demonstrated the ultimate limit of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 45 publications
(65 reference statements)
0
15
0
Order By: Relevance
“…[2][3][4] These surface effects become even more pronounced when scaling down in size. 5 The resulting capillary force may be used to manipulate 6 or fabricate [7][8] 3D objects, whereas it may be detrimental in the development of MEMS and NEMS. It also leads to artifacts in atomic force microscopy (AFM) imaging.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] These surface effects become even more pronounced when scaling down in size. 5 The resulting capillary force may be used to manipulate 6 or fabricate [7][8] 3D objects, whereas it may be detrimental in the development of MEMS and NEMS. It also leads to artifacts in atomic force microscopy (AFM) imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to rhodamine 6G, the buffer solution of the antibody was mixed with 20 wt% glycerol. Previous studies have already shown that glycerol-buffer mixtures can be used as a solvent for fluorescent proteins without any denaturation effects, structural changes or activity loss [ 2 , 22 ]. The loading procedure was similar to the rhodamine 6G experiment, and the results are shown in Fig 5a–5d as bright-field images and corresponding fluorescence images.…”
Section: Resultsmentioning
confidence: 99%
“…Microchanneled atomic force microscopy (AFM) micropipettes are a versatile nanodispensing (NADIS) system, which can deliver the smallest necessary volumes and has facilitated many applications in surface functionalization [ 1 , 2 ], adhesion [ 3 , 4 ], spatial cell manipulation [ 5 7 ], injection [ 5 , 8 ] and lithography/nanoprinting [ 9 ] in recent years. In the first NADIS experiments, the dispensing of liquid was limited by capillarity and the opening of the tip [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…After the sample has been dried, the nanopatterns can be characterized with a regular AFM probe after exchanging tips. Nanodispensing, as outlined in figure 4a, was used to deposit 25 nm polystyrene nanoparticles onto silicon oxide and glass substrates functionalized with aminopropyltriethoxysilane (APTES) through electrostatic interactions [44]. A drop of liquid was placed on top of a modified AFM cantilever with a channel for dispensing (Figure 4b).…”
Section: Nanodispensing Of Nanoparticles To Form Patternsmentioning
confidence: 99%
“…Overview of the Protocols Applied for Patterning and Characterizing Nanoparticles[44][45][46][47][48][49][50][51][52].…”
mentioning
confidence: 99%